Optimizing Vegetative Growth and Flowering in Fuchsia x hybrida: The Role of Media, Pinching, and Growth Regulators - , Choudhary Nandini Chandermohan; , Rajesh Thakur; , Puja Sharma; , Shreedhar Beese; , Nitin Sharma; , Suman Bhatia; , Rupali Thakur; , Babita Kanwar; , Sunita Devi (Archives of Current Research International, 2024)
The present investigation was carried out at the experimental farms of Horticultural Regional training station and Krishi Vigyan Kendra at Kandaghat (Solan) Himachal Pradesh, India under polyhouse conditions. It was laid out in a Completely Randomized Design (CRD) with 24 combinations of growing media M1: Soil+ Sand+ FYM (1:1:1v/v), M2:Cocopeat+Soil+Sand+ Leafmould+FYM (2:1:1:1v/v), M3:Cocopeat+Perlite+Vermiculite+Vermicompost (2:1:1:1 v/v), M4:Cocopeat + Vermicompost + Leafmould (2:1:1 v/v), growth regulator [G1: Control (0 ppm), G2:Benzyl adenine (150 ppm),G3: CPPU (10 ppm)] and pinching methods [P1:Single pinch and P2:Double pinch] which were replicated thrice each having 10 pots accommodating one plant per pot. Plants were raised through terminal cutting and were planted in 6-inch size pots. Study revealed that maximum plant height (33.13 cm), plant spread (33.37 cm), length of side shoots (24.67 cm) and minimum number of days taken for visible bud formation (92.40 days), number of days taken for peak flowering (160.60 days) was recorded when the single pinched plants were grown in media consisting cocopeat + Vermicompost + Leafmould (2:1:1 v/v) and sprayed with 150 ppm of benzyl adenine. However, maximum number of side shoots (27.33), number of flowers per plant (55.67), number of flowers per plant open at a time (42.93), duration of flowering (24.67days) was recorded when double pinched plants were grown in growing media consisting of cocopeat + vermicompost + Leafmould (2:1:1 v/v) and were sprayed with 150 ppm of benzyl adenine. The maximum flower diameter (4.61 cm) was recorded when single pinched plants were grown in medium consisting cocopeat + vermicompost + leafmould (2:1:1 v/v) and sprayed with 10 ppm of CPPU. Based on the present investigation findings, double pinched plants of Fuchsia x hybrida grown in pots consisting of growing media i.e., cocopeat + vermicompost+ leafmould (2:1:1 v/v), sprayed with 150 ppm of benzyl adenine is recommended to obtain quantitative and attractive pot plants of Fuchsia x hybrida.